An investigation on the effects of Afrocentric missense variations on the structure and function of CYP2A6 protein - Makombe, Chipo Perpetual (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
Pharmacogenomics, the foundation of personalized medicine distinguishes patients into different categories based on their response to the risk of a disease. Cytochrome P450 (CYPs) proteins are a family of enzymes critical in the metabolism of drugs and other substances. Genetic polymorphisms in CYPs can result in different enzymatic activity in individuals influencing the efficacy and toxicity of drugs. One of the CYPs which primarily metabolizes nicotine and other pharmaceutical drugs such as Artemisinin and Artesunate, Pilocarpine, Valproic Acid and Letrozole is CYP2A6. The gene encoding the protein is highly polymorphic and this can affect the rate of metabolism of drugs in individuals. Previously most studies unveiled connections between CYP2A6 variants and nicotine. Implications concerning the effects of specific missense variations in CYP2A6 drug metabolism have deficiencies. This study aimed to critically examine the structural and functional implications of 13 CYP2A6 allele variations on CYP2A6 protein using Bioinformatics techniques. Methods used were template selection, mutagenesis, parameter assignment and protonation. Molecular Dynamics to get insights regarding protein behavior at an atomic level, clustering to identify conformations during a simulation and DSSP for secondary structure analysis to monitor how secondary structures evolve. Berendsen and Parinello-Rahman barostats at production run were used for comparison. A global analysis was conducted to identify structural transitions (RMSD, RMSF, and Rg), clustering, and secondary structure prediction. Results from Berendsen barostat were inconsistent compared to Parrinello-Rahman barostat implying that CYP2A6 is sensitive to the pressure coupling parameter for precise and accurate results. Our clustering results showed each system in one conformation, fluctuations and shifts on the C-D, H-I loops and F, G, and L helices on variants I149M, F118l, K476R, and E390K_N418D_E419D. This indicated a potential loss of function limiting the protein's ability to conformational flexibility for catalysis and substrate recognition. Certain regions of CYP2A6 became more rigid due to variations, which could have a negative impact on the catalytic activity, regulatory interactions, and general function of the enzyme in metabolism. Globally the variations did not cause large changes to the protein, there is need for a local analysis using Dynamic Residue Networks to study how residue interactions affect the function of CYP2A6.
Keywords: Missense mutation; Structural dynamics; Enzyme activity; Drugs -- Metabolism; CYP2A6